Pharmaceutico-analytical Standardisation of Tripurabhairava Rasa and Evaluation of its Acute Oral Toxicity, Antipyretic, and Analgesic Activities in Wistar Albino Rats: A Research Protocol of Experimental Study - Sukeshini Julme; Mujahid Khan (Journal of Clinical and Diagnostic Research)
Introduction: Tripurabhairava Rasa, a herbo-mineral compound from Bharat Bhaishajya Ratnakar, is used to treat all types of Jwara (fever). Fever is a natural defence against infections, but elevated temperatures can sometimes cause harm, necessitating antipyretic treatment. Tripurabhairava Rasa is made from Shuddha Vatsanabha (Aconitum ferox), Shunthi (Zingiber officinale), Maricha (Piper nigrum Linn.), and Shuddha Tankan (Borax). Given it composition, especially Vatsanabha, a toxicity study is necessary. In addition to determining the drug’s safety, studies are being conducted to discover any potential side effects. Need of the study: This study is essential because Tripurabhairava Rasa, a traditional Ayurvedic formulation for treating fever, has not been systematically prepared, standardised, or scientifically evaluated. The lack of pharmaceutical and analytical standardisation raises concerns about its safety, consistency, and efficacy. With the growing interest in integrating traditional medicine into modern healthcare, scientific validation is crucial. Evaluating the formulation’s preparation, acute oral toxicity, antipyretic, and analgesic effects in Wistar albino rats will provide the necessary evidence to ensure its safe and effective use in clinical practice. Aim: To conduct pharmaceutical and analytical standardisation of Tripurabhairava Rasa, along with evaluating its acute oral toxicity, antipyretic, and analgesic activities in Wistar albino rats. Materials and Methods: This experimental study is planned to take place from January 2024 to April 2024 at the animal house of Datta Meghe College of Pharmacy, Datta Meghe Institute of Higher Education and Research (Deemed to be University), Wardha, Maharashtra, India. Vatsanabha and Tankan will be collected from Cotex Laxmi Health Care Pvt. Ltd., while Shunthi, Maricha, Nagavalli, Ardraka, and Nimbu will be collected from the local market, with brewers’ yeast of API grade procured from Merck. Raw drugs will be verified and authenticated by the taxonomist/Dravyaguna department, and standardisation will be conducted in accordance with Active Pharmaceutical Ingredient (API) or analytical labs at MGACH and RC. This study will follow Organisation for Economic Co-operation and Development (OECD) guidelines 423 and will involve 54 rats. Further analysis and experimentation will be conducted at a laboratory or research institute of national repute as listed in the DMIHER (DU) profile. The organoleptic and physicochemical characteristics of Tripurabhairava Rasa will be studied.